Genome-wide identification and expression analysis of the CONSTANS-like family in potato (Solanum tuberosum L.) - Yin, Wang; Wang, Luo; Shu, Qiqiong; Chen, Mingjun; Li, Fei; Luo, Xiaobo (Frontiers in Genetics, 2024)
The CONSTANS-like (COL) gene plays important roles in plant growth, development, and abiotic stress. A total of 15 COL genes are unevenly distributed on eight chromosomes in the potato genome. The amino acid length of the family members was 347–453 aa, the molecular weight was 38.65–49.92 kD, and the isoelectric point was 5.13–6.09. The StCOL family can be divided into three subfamilies by evolutionary tree analysis, with conserved motifs and similar gene structure positions in each subfamily. The analysis of promoter cis-acting elements showed 17 cis-acting elements related to plant hormones, stress, and light response. Collinearity analysis of COL genes of tomato, potato, and Arabidopsis showed that 13 StCOL genes in the different species may have a common ancestor. A total of 10 conserved motifs and six kinds of post-translational modifications in the 15 StCOL proteins were identified. The 15 StCOL genes exhibit a genomic structure consisting of exons and introns, typically ranging from two to four in number. The results showed that 10 genes displayed significant expression across all potato tissues, while the remaining five genes were down-expressed in potato transcriptome data. The quantitative reverse transcription polymerase chain reaction (qRT-PCR) analysis exhibited differential expression of 8 StCOL genes in the potato leaves and tubers at different growth stages, as well as 7 StCOL genes under 2°C treatment conditions. These results suggested that the StCOL gene family may play an important role in regulating potato tuberization and responding to cold stress.